A1.27 Serum rituximab level and other predictors for good eular response before re-treatment in rheumatoid arthritis. (31st January 2014) - Mazilu, Diana; Gainaru, Cecilia; Apetrei, Natalia; Luca, Georgiana; Gudu, Tania; Peltea, Alexandra; Groseanu, Laura; Constantinescu, Cosmin; Saulescu, Ioana; Bojinca, Violeta; Balanescu, Andra; Predeteanu, Denisa; et al.
Abstract : Background and Objectives: Predictive factors for rituximab (RTX) response in rheumatoid arthritis (RA) patients are currently still under debate. Repeated re-treatment is now the rule, but it is worth knowing if there are predictive factors for good or moderate EULAR response after a new course of RTX. Materials and Methods: Twenty five long term RTX-treated patients with RA were included in this prospective study. Their average time with RTX treatment was 41.79 months. RTX serum level was measured by sandwich ELISA (Promonitor-RTX Ref. PG-PRTX-12700), after 6 months from last re-treatment. Patients were divided into detectable versus non-detectable drug levels based on assay cut-off. Clinical and pharmacological data were collected at the time of dosing serum RTX level and 6 months later. Results: At 6-month follow-up, 8 (32%) of the RA patients have achieved a good EULAR response and 7 patients (28%) - a moderate EULAR response. Regarding the serum RTX level, 9 patients (36%) had no detectable drug level. From this group at 6 month after last infusion, 6 (66.6%) patients had no EULAR response. All patients tested negative for anti-RTX antibodies. A significant correlation was found between detectable drug level and EULAR response after re-treatment (p = 0.034, r = 0.424). Patient status of anti-citrullinated protein antibodies (ACPA) was strongly correlated to RTX drug level (p = 0.021, r = 0.460) but not to the EULAR response (p = 0.216, r = 0.256). Another interesting finding was the significant correlation between RTX serum level and number of previous anti tumor necrosis agents used before RTX was initiated (p = 0.009, r = 0.514). Conclusions: This observational study suggests that detectable RTX serum level before re-treatment can be predictive for a good EULAR response at 6 month. ACPA positivity and higher number of previous anti TNF agents used are correlated with RTX level. As non-detectable RTX level increases chances for no response, drug level monitoring may be used to optimise treatment in patients with RA.